Physics for scientists and engineers - Raymond A. Serway (Thomson-Brooks/Cole, 2004)
NOT SOLD SEPARATELY. PHYSICS FOR SCIENTISTS AND ENGINEERS, 6th maintains the Serway traditions of concise writing for the students, carefully thought-out problem sets and worked examples, and evolving educational pedagogy. This edition introduces a new co-author, Dr. John Jewett, at Cal Poly ? Pomona, known best for his teaching awards and his role in the recently published PRINCIPLES OF PHYSICS, 3rd, also written with Ray Serway. This authoritative text, along with the newly enhanced supplemental package for instructors and students, provides students with the best in introductory physics education. Providing students with the tools they need to succeed in introductory physics, the 6th edition of this authoritative text features unparalleled media integration and a newly enhanced supplemental package for instructors and students!